Coral reef and reef fishes of core zone in the marine proctected areas of Aceh Besar, Indonesia. Issue 1 (February 2021) - Muhammad, M; Firdaus, R; Kurnianda, V; Jalil, Z; 'Akla, C M N; Dewi, I J P
Abstract: This research was conducted in January 2018 in the core zone of the Marine Protected Areas Peukan Bada and Lhoknga, Aceh Besar. The purpose of this study was to determine the coral reef cover and the abundance of reef fish in the core zone areas. The method of collecting coral reef cover data used the transect photo. Further, we analyzed these data using CPCe 4.1 software with a uniform grid technique. Moreover, the collection of coral fish abundance data using the Visual Census. The results of the study showed that the coral reef cover in the core zone of Lhoknga and Lampuuk water is 35.36% and 43.09% which are categorized as "moderate damage" with an abundance of reef fish value are 23900 Ind/Ha and 43600 Ind/Ha, respectively. On the other hand, the coral reef cover in the core zone of Bunta Island waters was 64.91% which was categorized as "good" with an abundance of reef fish value is 28600 Ind/Ha. However, the coral reef cover in the core zone of Batee Island waters was 23.68% which was categorized as "badly damage" with an abundance of reef fish value is 29300 Ind/Ha. In addition, the coral reef cover in the core zone of Tuan Island waters was 25.87% which was categorized as "moderate damage" with an abundance of reef fish value is 58100 In/Ha. Based on the results, the data conclude that the condition of coral reefs in the Marine Protected Area in the Lhoknga, Lampuuk, and Batee Island water requires proper handling in improving natural resources in their core zone.